(untitled) (International journal of artificial intelligence, 2026)
Antibiotic resistance has emerged as one of the most critical challenges facing modern medicine. The increasing prevalence of resistant bacterial pathogens threatens the effectiveness of standard antimicrobial therapies and compromises clinical outcomes across a wide range of infectious diseases. This article explores antibiotic resistance as a multidimensional clinical problem, linking molecular mechanisms of resistance with their direct implications for diagnosis, treatment, and patient care. Emphasis is placed on the importance of rational antibiotic use and evidence-based decision-making at the bedside to combat the growing burden of resistant infections.